Pose-varied multi-axis optical finishing systems theory and process validation - Cheng, Haobo (Springer Berlin Heidelberg, 2015)
Focuses on advanced optical finishing techniques and design for high-performance manufacturing systems. It provides numerous detailed examples of how advanced automation techniques have been applied to optical fabrication processes. The simulations, removal rate and accurate experimental results offer useful resources for engineering practice. Researchers, engineers and graduate students working in optical engineering and precision manufacture engineering will benefit from this book.